1985
DOI: 10.1016/s0022-5347(17)47739-1
|View full text |Cite
|
Sign up to set email alerts
|

Human Tumor Cell Destruction by Distilled Water: An in Vitro Evaluation

Abstract: A distilled water lavage is sometimes used during tumor surgery in an effort to kill tumor cells spilled into a cavity or wound. To test the efficacy of this technique, a model study utilized nine different human tumor cell lines, subjected in v i m to hypotonic exposure for I to 10 minutes. Only the carcinoid, multiple myeloma, leiomyosarcoma cell lines, and normal lymphocytes were destroyed by the treatment. Although breast, ovarian, gastric, bladder, and melanoma cell lines were damaged to varying degrees, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…observed a decrease in DNA synthesis in different tumour cell lines after exposure to distilled water for 1–10 min. However, the remaining cells did not lose their replication capacity . As distilled water has the characteristic for hypotonic, but no data are available supporting this hypothesis that cancer cell injury was related to distilled water in surgery of tumour resection.…”
Section: Discussionmentioning
confidence: 96%
“…observed a decrease in DNA synthesis in different tumour cell lines after exposure to distilled water for 1–10 min. However, the remaining cells did not lose their replication capacity . As distilled water has the characteristic for hypotonic, but no data are available supporting this hypothesis that cancer cell injury was related to distilled water in surgery of tumour resection.…”
Section: Discussionmentioning
confidence: 96%
“…While this practice is not unique to our institution or urology, there is little evidence to suggest the utility of this practice or appropriate duration of this treatment to have an effect on bladder cancer cell death. 7 Prior research studies in colorectal and ovarian cancer show conflicting results in regards to the cytolytic efficacy of intraperitoneal lavage with sterile water. 12,13 Furthermore, prior bladder cancer research has demonstrated conflicting evidence regarding the role of intraperitoneal lavage with sterile water.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Furthermore, prior bladder cancer research has demonstrated conflicting evidence regarding the role of intraperitoneal lavage with sterile water. [7][8][9] Our study was specifically intended to study the time course of events in bladder cancer cells after exposure to water. First, we confirmed the cytocidal effect of hypotonic shock induced by sterile water on bladder cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations